An unusual presentation of atrioventricular nodal reentrant tachycardia - Ghitun, Florina-Adriana; Ailoaei, Stefan; Ursu, Dan; Chistol, Raluca; Tinica, Grigore; Statescu, Cristian; Grecu, Mihaela (Journal of Cardiology and Cardiovascular Medicine, 2021)
Introduction: Atrioventricular nodal reentrant tachycardia (AVNRT) is the most frequent supraventricular tachycardia, commonly manifesting as autolimited paroxysmal episodes of rapid regular palpitations that exceed 150 beats per minute (bpm), dizziness and pounding neck sensation. Case presentation: We present a case of a male patient, 70 years old, with ischemic heart disease and slow-fast AVNRT treated with radiofrequency catheter ablation (RFCA) in March 2019, with regular 6-months follow-ups. He was readmitted in our department in November 2020 for rest dyspnea and incessant fluttering sensation in the neck, without palpitations. The event electrocardiogram (ECG) was initially interpreted by general cardiologist as accelerated junctional rhythm, 75 bpm. Due to the persistence of symptoms and ECG findings, a differential diagnosis between reentry and focal automaticity was imposed. The response to vagal maneuvers and Holter ECG monitoring characteristics provided valuable information. We suspected recurrent slow ventricular rate typical AVNRT, which was confirmed by electrophysiological study and we successfully performed the RFCA of the slow intranodal pathway. Conclusion: AV nodal reentry tachycardia may have an unusual presentation, occurring in elder male patients with structural heart disease. Antiarrhythmic drugs can promote reentry in this kind of patients. In cases of slow ventricular rate, vagal maneuvers and Holter ECG monitoring can help with the differential diagnosis. The arrhythmia can be successfully treated with RFCA with special caution regarding the risk of AV block.